ANALISIS FAKTOR KESULITAN GURU TMI AL-AMIEN PRENDUAN DALAM MENCAPAI SKOR MAKSIMAL PADA TEST TOAFL DI PONDOK PESANTREN AL-AMIEN PRENDUAN SUMENEP MADURA - Yakin, Ainul; Salim, Aisyah Amalia (Reflektika, 2024)
This study aims to analyze the difficulty factors experienced by Tarbiyatul Mu'allimien Al-Islamiyah (TMI) Al-Amien Prenduan teachers in achieving the maximum score on the TOAFL test at Al-Amien Prenduan Islamic Boarding School, Sumenep, Madura. This research focuses on two questions: 1. What do TMI teachers experience as the difficulty factors in achieving maximum scores on the TOAFL test? 2. What are the solutions to overcome the difficulties faced by TMI Al-Amien Prenduan teachers in achieving maximum scores on the TOAFL test? This research employs a descriptive qualitative approach, with the primary instruments being in-depth interviews and documentation. The results showed that the difficulty factors faced included limited vocabulary mastery, weaknesses in grammar (nahwu and sharaf), a lack of supporting resources such as teaching materials and test simulations, and unfamiliarity with using technology for computer-based exams. In addition, psychological factors, such as anxiety and a lack of time management during the exam, also affected the results achieved. To overcome these difficulties, the study recommends enhancing basic Arabic language skills through intensive training, providing relevant teaching materials, conducting periodic test simulations, and training in technology skills. This comprehensive approach is expected to help TMI Al-Amien Prenduan teachers achieve maximum scores, improve their competencies, and support the quality of education in pesantren.